Healthy Living: Dietary Supplement Labels Word Search - Karla P. Shelnutt (EDIS)
FCS-8854, a 1-page handout by Karla P. Shelnutt, is the English language version of FCS8854-Span, Vida Saludable: Etiquetas de Suplementos Dietéticos Búsqueda por Palabras. It helps familiarize readers with the terminology used on dietary supplement labels. Published by the UF Department of Family Youth and Community Sciences, June 2008.